A Comparative Study of Missionary Routes in Modern History: The Cases of Timothy Richard and James Hudson Taylor - LIU , Aixin (Journal of Research for Christianity in China (JRCC), 2025)
The differing missionary approaches of Timothy Richard and James Hudson Taylor reflect their distinct theological orientations and represent their contrasting contextualization strategies toward diverse missionary contexts. This paper aims to examine the missionary journeys of these two Western missionaries to China, summarizing the characteristics of their respective missionary paths and strategies while exploring the underlying theological motivations and missionary visions driving their work.